Complications of Glaucoma Surgery. - Feldman, Robert M. MD (Oxford University Press, 2012)
This book provides clear and detailed guidelines on the management of complications in glaucoma surgery. Coverage spans the entire spectrum of glaucoma, including descriptions of traditional and newly emerging modalities available for surgeons.